Does the Jakarta Islamic Index Reflect Efficient Market? Insights from Calendar Effects and Volatility Modelling - Purwanto Widodo; Faizi Faizi; Airlangga Surya Kusuma (Journal of Social Commerce, 2025)
This study examines the efficiency of the Jakarta Islamic Index (JII) by testing for anomalies such as the Day of the Week Effect, Monday Effect, Friday Effect, and Week-Four Effect, both under normal conditions and during the Covid-19 crisis. This study seeks to determine whether JII adheres to the Efficient Market Hypothesis (EMH) or exhibits predictable patterns in stock returns. The study utilizes daily return data from JII, covering periods before (January 2008–February 2020), during (March 2020–December 2022), and combined before and during the Covid-19 crisis. Stationarity tests (Augmented Dickey-Fuller and Philips–Perron) were conducted, followed by ARMA/ARIMA modelling to address autocorrelation and heteroscedasticity. ARCH-GARCH models, including EGARCH, TARCH, and PARCH, were employed to analyze the volatility and leverage effects. Dummy variables for trading days and weeks are used to test for anomalies.  The results confirm the presence of the day of the week, Monday, and Week four effects in JII returns, indicating market inefficiency. However, the Covid-19 crisis did not significantly alter return patterns, suggesting resilience in the Islamic stock market. The study also identifies asymmetric volatility responses, with EGARCH (1,1) being the most suitable model, following a non-normal distribution (GED). These findings align with some prior research but contrast with others, highlighting mixed evidence on market anomalies in Islamic indices.